Preparation of polypyrrole/nanosilica composite for solid-phase microextraction of bisphenol and phthalates migrated from containers to eye drops and injection solutions - Mehdi Ansari Dogaheh; Mansoureh Behzadi (Elsevier, 2019)
This paper describes the electrodeposition of polyphosphate-doped polypyrrole/nanosilica nanocomposite coating on steel wire for direct solid-phase microextraction of bisphenol A and five phthalates. We optimized influencing parameters on the extraction efficiency and morphology of the nanocomposite such as deposition potential, concentration of pyrrole and polyphosphate, deposition time and the nanosilica amount. Under the optimized conditions, characterization of the nanocomposite was investigated by scanning electron microscopy and Fourier transform infra-red spectroscopy. Also, the factors related to the solid-phase microextraction method including desorption temperature and time, extraction temperature and time, ionic strength and pH were studied in detail. Subsequently, the proposed method was validated by gas chromatography-mass spectrometry by thermal desorption and acceptable figures of merit were obtained. The linearity of the calibration curves was between 0.01 and 50 ng/mL with acceptable correlation coefficients (0.9956-0.9987) and limits of detection were in the range 0.002-0.01 ng/mL. Relative standard deviations in terms of intra-day and inter-day by five replicate analyses from aqueous solutions containing 0.1 ng/mL of target analytes were in the range 3.3%-5.4% and 5%-7.1%, respectively. Fiber-to-fiber reproducibilities were measured for three different fibers prepared in the same conditions and the results were between 7.3% and 9.8%. Also, extraction recoveries at two different concentrations were ≥96%. Finally, the suitability of the proposed method was demonstrated through its application to the analysis of some eye drops and injection solutions. Keywords: Solid-phase microextraction, Gas chromatography-mass spectrometry, Polyphosphate-doped polypyrrole, Nanosilica, Phthalates, Bisphenol A